The Use of Opioids for Treatment of Pediatric Neuropathic Pain: A Literature Review. Issue 6 (June 2019) - Windsor, Robert B.; Tham, See Wan; Adams, Trevor L.; Anderson, Annette
Abstract : Pediatric neuropathic pain is caused by a spectrum of disorders that are generally challenging to treat. Many of the underlying altered neurological processes are being elucidated through mechanistic studies. Few randomized control trials have evaluated the use of opioids for the treatment of adult neuropathic pain conditions, and there have been none in pediatric populations. With sparse data to provide guidance and an incomplete understanding of the underlying mechanisms, the use of opioids remains unclear. Our clinical experience and typical risk versus benefit considerations suggest a limited, if any, role for using opioids to treat pediatric neuropathic pain. In this literature review, we review the available adult and pediatric data and provide general guidance on this subject matter.